2019
DOI: 10.1111/aogs.13636
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypocalcemia during surgery for placenta accreta spectrum: The case for empiric replacement

Abstract: Introduction We aimed to determine predictive factors for severe hypocalcemia in women with placenta accreta spectrum. Material and methods Study of 123 women with histology‐proven placenta accreta spectrum with cesarean hysterectomy between 2011 and 2017. Two groups were selected: Cases: critically low (“panic value”) serum total calcium (≤7 mg/dL) and Controls: normal serum total calcium (≥8.5 mg/dL). Regression and receiver operating characteristic (ROC) analyses were performed to evaluate the potential ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The sonographic criteria suggestive of atelectasis used included “lung volume loss” with displacement of adjacent structures 11 . Hypocalcemia was defined as serum total calcium measurement ≤7 mg/dl or ≤1.75 mmol/L 13 …”
Section: Methodsmentioning
confidence: 99%
“…The sonographic criteria suggestive of atelectasis used included “lung volume loss” with displacement of adjacent structures 11 . Hypocalcemia was defined as serum total calcium measurement ≤7 mg/dl or ≤1.75 mmol/L 13 …”
Section: Methodsmentioning
confidence: 99%
“…Levin and Rottenstreich and Drs. Matsubara et al for their letters about our recently published research article . We are happy to address their concerns:…”
mentioning
confidence: 92%
“…7 Differences in clinical significance between the trauma and perioperative populations are hypothesised to result from alterations in citrate clearance secondary to hypotension, acidosis, and hypothermia in the trauma cohort. 6 Recent studies on intraoperative and perioperative massive resuscitation have been limited to specific surgeries, such as abdominal aortic aneurysm, 8 placenta accreta, 9 or liver transplantation, 10 which may not be widely generalizable. The largest study in non-cardiac surgery patients found that transfusion with 5 or more units of red blood cells was associated with increased 30-day mortality and greater rate of postoperative complications, however, this study did not specifically characterise the incidence and risk factors for abnormalities, like hypocalcaemia, in the massive transfusion population.…”
Section: Introductionmentioning
confidence: 99%